Novel Methodology toward Nearly Zero Energy Building (NZEB) Renovation: Cost-Effective Balance Approach as a Pre-Step to Cost-Optimal Life Cycle Cost Assessment - Yovko Ivanov Antonov; Per Kvols Heiselberg; Michal Zbigniew Pomianowski (Applied Sciences, 2021)
Reaching environmental targets set by the European Union (EU) requires a constant renovation of the existing building stock to nearly Zero Energy Buildings (NZEB) in a cost-optimal manner. Studies show that the renovation rate of the existing building stock is more than two times less than what is necessary to reach the targets. Furthermore, the majority of performed renovations across the EU reach just a small amount of energy savings, whereas NZEB renovations are rarely achieved. This paper proposes a methodology for the evaluation of renovation measures, aiming to provide decision support related to the selection of what to renovate and to what extent. The proposed method is rooted in the well-established cost-optimal methodology, yet it suggests a pre-step to package evaluation. This is done by means of a simplified cost-effective parameter (CEP), linking cost, lifetime, and energy savings. The methodology is demonstrated using a case study building in Denmark. The results show that the CEP provides good grounds for the compilation of single actions to packages. Further developments could focus on the sensitivity of the model inputs and integration of additional evaluation parameters to cost, such as environmental, architectural, comfort, risk, etc.